Bale Balaq: A Local Wisdom-based Construction with Earthquake Resistance in North Lombok, West Nusa Tenggara, Indonesia - Anggraeni, Peri; Syarifuddin, Syarifuddin; Inderasari, Oryza Pneumatica (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2024)
Bale Balaq is a traditional house construction built based on the local wisdom of the Sasak tribe. The Malaka village community is one of the Sasak tribe communities that still use Bale Balaq as their residential dwelling. This study uses a qualitative, phenomenological approach. The findings describe that the design of the Bale Balaq building is based on local wisdom, including the materials used in its construction, such as wood, thatch, bobok (coconut leaves), and bamboo, as well as the rules governing the construction of Bale Balaq. Bale Balaq is not just a place to live; each structure within Bale Balaq holds philosophical values that serve as a way of life. Bale Balaq is interpreted as a character that reflects identity, provides safety for those living within it, and offers comfort to its inhabitants. Moreover, Bale Balaq is resistant to disasters such as earthquakes.